‘Participating Immortality’: Memory and Performance in Middleton's Hengist, King of Kent - Paul, J. Gavin (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
Middleton's Hengist, King of Kent and its multifaceted textual afterlives dramatize memorial processes, greatly dependent on the participatory experience of the formed event. These processes highlight not only that theatrical production is a means for preserving cultural memories, but also that the preservation of the past is inseparable from, and conflated with, the production of new theatrical memories. Remembering the past in the theatre — in the fullest sense of ‘re-membering’ as imaginatively putting dead bodies back together — goes hand in hand with the necessity of remembering the theatrical past, of recalling the play that vanished even as it came into being.